Trans-resveratrol induces a potential anti-lipogenic effect in lipopolysaccharide-stimulated enterocytes - Etxeberria, U; Castilla-Madrigal, R; Lostao, M P; Martínez, J A; Milagro, F I (Cellular and Molecular Biology, 2015)
A DNA microarray analysis was conducted in Caco-2 cells to analyse the protective effects of trans-resveratrol on enterocyte physiology and metabolism in pro-inflammatory conditions. Cells were pre-treated with 50 Î¼Îœ of trans-resveratrol and, subsequently, lipopolysaccharide (LPS) was added for 48 h. The microarray analysis revealed 121 genes differentially expressed between resveratrol-treated and non-treated cells (B> 0, is the odd thatthe gene is differentially expressed). Inhibitor of DNA binding 1 (ID1), histidine-rich glycoprotein (HRG), NADPH oxidase (NOX1) and sprouty homolog 1 (SPRY), were upregulated by LPS treatment, but significantly blocked by trans-resveratrol pre-treatment (padj< 0.05, after adjusting for Benjamini-Hocheberg procedure). Moreover, genes implicated in synthesis of lipids (z-score= -1.195) and concentration of cholesterol (z-score= -0.109), were markedly downregulated by trans-resveratrol. Other genes involved in fat turnover, but also in cell death and survival function, such as transcription factors Krüppel-like factor 5 (KLF5) and amphiregulin (AREG), were also significantly inhibited by trans-resveratrol pre-treatment. RT-qPCR-data confirmed the microarray results. Special mention deserves acyl-CoA synthetase long-chain family member 3 (ACSL3) and endothelial lipase (LIPG), which were downregulated by this stilbene and have been previously associated with fatty acid synthesis and obesity in other tissues. This study envisages that trans-resveratrol might exert an important anti-lipogenic effect at intestinal level under pro-inflammatory conditions, which has not been previously described.